Pemasaran Pariwisata Berkelanjutan Perusahaan Sosial ”Eco Tourism Bali” Melalui Program Eco Climate Bade Di Kaamala Resort Ubud (Jurnal Destinasi Pariwisata, 2025)
This study aims to identify sustainable tourism marketing conducted by the social enterprise Eco Tourism Bali (ETB) through the Eco Climate Badge program at Kaamala Resort Ubud. The research employs a qualitative method with data collection techniques including in-depth interviews, observations, literature reviews, and interactive data analysis. The findings reveal that ETB's products include the Eco Climate Badge, Regenerative Bali Program, Sustainable Event Management, and Training Program, with the Eco Climate Badge as the flagship program a certification system awarded to hotels and restaurants that implement environmentally friendly practices. Sustainable tourism promotion is dominated by digital channels such as social media and websites, as well as offline through two main activities: World Tourism Day and Eco Tourism Week. Product pricing is flexible and inclusive, while distribution is focused on digital platforms. The implementation of the Eco Climate Badge at Kaamala Resort Ubud includes energy efficiency, waste reduction, biodiversity conservation, and social benefits for the local community. This study concludes that sustainability-based marketing can create a positive image and attract environmentally conscious tourists. The study also encourages other social enterprises to develop similar programs to support sustainable tourism that aligns with community needs.